The radial forearm snake flap: A novel approach to oral cavity and oropharyngeal reconstruction that reduces forearm donor site morbidity. Issue 1 (9th June 2015) - Garg, Ravi K.; Wieland, Aaron M.; Poore, Samuel O.; Sanchez, Ruston; Hartig, Gregory K.
Abstract : Background: Radial forearm free flaps are a versatile option for head and neck reconstruction, but often complicated by donor‐site problems including skin‐graft loss and wound breakdown. We introduce the radial forearm "snake" flap as a technique enabling primary donor site closure and compare wound healing outcomes to flap donor sites requiring split thickness skin graft (STSG) closure. Patients and Methods: A review of all radial forearm free flaps harvested over a 5‐year period was performed. We identified 18 radial forearm snake flaps whose donor sites were closed primarily. These flaps were designed as a long, narrow ellipse parallel to the forearm. An additional 57 forearm flaps were identified whose donor sites were closed with STSGs. Patient demographics, free flap survival rates, and wound healing complications were compared. Results: The survival rate for radial forearm snake flaps was 100% compared to 98.2% for wider radial forearm flaps ( P = 1.00). There were 8 tendon exposures at the donor site, all of which occurred in patients whose donor sites were closed with STSGs. Delayed wound healing occurred in 1 radial forearm snake flap donor site (5.6%) compared to 18 (31.6%) donor sites closed with STSGs ( P = 0.03). Conclusions: Radial forearm snake flaps are useful for reconstruction of small to medium size defects of the oral cavity and oropharynx and enable primary donor site closure. Flap success rates are not compromised by raising a radial forearm snake flap and rates of delayed healing of the flap donor site are significantly reduced compared to forearm flap donor sites closed with STSGs. © 2014 Wiley Periodicals, Inc. Microsurgery 37:6–11, 2017.